If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 53 + -1x Solving 12 = 53 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 12 + x = 53 + -1x + x Combine like terms: -1x + x = 0 12 + x = 53 + 0 12 + x = 53 Add '-12' to each side of the equation. 12 + -12 + x = 53 + -12 Combine like terms: 12 + -12 = 0 0 + x = 53 + -12 x = 53 + -12 Combine like terms: 53 + -12 = 41 x = 41 Simplifying x = 41
| 2x^2-32=1150 | | 6=s+5 | | 7x+5=-10+7x | | -7x=-41x+66 | | 3k-3-6k+6=24 | | 12.50+7.25=32050+5.25 | | (17x-2)+25=(3x+2)-12x | | 24s+9=(240)+9 | | 3(2x+5)=5x+3-3x | | 2(5x)+2(6x)+2(5*6)=5*6*x | | X-(-7)=20 | | x+8=-3x+4 | | (-10x+14)=-76 | | -15x-5+5x^2=x^2-8-2x | | -52=2+3p | | 4(5x+8)=6(3x-6) | | 5y+(-3x)-9x+1-2y+8= | | 2(9x)+2(4x)+2(9*4)=9*4*x | | 2.35*5= | | 15+2.03*5= | | 4x+y+6=0 | | 2x^2-3=-131 | | 15+2.03*9= | | x+6=-3x+10 | | 25=5x-4 | | 2(3x)+2(11x)+2(3*11)=11*3*x | | 2.35*9= | | Y=x+2z | | -9c+6d=8 | | 14=4-4n-2 | | 3(a+3)-a=10+a-4 | | (-4-3n)-8=128 |